Kontribusi Semiotika dalam Kajian Islam - Muthiah Mufidah (JURNAL INDO-ISLAMIKA, 2011)
This paper will explain the contribution of semiotic studies in Islamic studies, especially the Qur'an. This research is a qualitative research. The data collection method of this paper is the study of literature, which is collecting data from all books, journals, and literature related to the research theme. The author concludes that semiotics -as one of the disciplines of science- can be used as an approach in the study of the Qur'an.